Evolution by Pervasive Gene Fusion in Antibiotic Resistance and Antibiotic Synthesizing Genes - Orla Coleman; Ruth Hogan; Nicole McGoldrick; Niamh Rudden; James O. McInerney (Computation, 2015)
Phylogenetic (tree-based) approaches to understanding evolutionary history are unable to incorporate convergent evolutionary events where two genes merge into one. In this study, as exemplars of what can be achieved when a tree is not assumed a priori, we have analysed the evolutionary histories of polyketide synthase genes and antibiotic resistance genes and have shown that their history is replete with convergent events as well as divergent events. We demonstrate that the overall histories of these genes more closely resembles the remodelling that might be seen with the children’s toy Lego, than the standard model of the phylogenetic tree. This work demonstrates further that genes can act as public goods, available for re-use and incorporation into other genetic goods.